The cutoff values of indirect indices for measuring insulin resistance for metabolic syndrome in Korean children and adolescents - Jun Woo Kim; Sang Hoo Park; Yoojin Kim; Minji Im; Heon-Seok Han (Korean Society of Pediatric Endocrinology, 2016)
PurposeThe prevalence rates of metabolic syndrome (MetS) and percentile distribution of insulin resistance (IR) among Korean children and adolescents were investigated. The cutoff values of IR were calculated to identify high-risk MetS groups.MethodsData from 3,313 Korean subjects (1,756 boys and 1,557 girls, aged 10-18 years) were included from the Korean National Health and Nutrition Examination Survey conducted during 2007-2010. Three different sets of criteria for MetS were used. Indirect measures of IR were homeostasis model assessment (HOMA-IR) and triglyceride and glucose (TyG) index. The cutoff values of the HOMA-IR and TyG index were obtained from the receiver operation characteristic curves.ResultsAccording to the MetS criteria of de Ferranti el al., Cook et al., and the International Diabetes Federation, the prevalence rates in males and females were 13.9% and 12.3%, 4.6% and 3.6%, and 1.4% and 1.8%, respectively. Uses these 3 criteria, the cutoff values of the HOMA-IR and TyG index were 2.94 and 8.41, 3.29 and 8.38, and 3.54 and 8.66, respectively. The cutoff values using each of the 3 criteria approximately corresponds to the 50th-75th, 75th, and 75th-90th percentiles of normal HOMA-IR and TyG index levels.ConclusionThis study describes the prevalence rates of MetS in Korean children and adolescents, an index of IR, and the cutoff values for MetS with the aim of detecting high-risk groups. The usefulness of these criteria needs to be verified by further evaluation.